Zastosowanie metod pokojowego rozstrzygania sporów w konflikcie o Górski Karabach - Kolarz, Stefania (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Over twenty years ago the Armenians inhabiting one of Azerbaijani provinces declared constitution of a new state — the Nagorno-Karabakh Republic. Hence, the conflict over legal status of this region begun; formally the terrain belongs to Azerbaijan, but it remains under Armenian control. The international community multiplied attempts of mediation and created a Group of Minsk under auspices of OSCE especially for the purpose of resolution of the karabakhi dispute. However, any settlement wasn’t reached so far. Therefore, one may ask whether this conflict may be solved using diplomatic means of international disputes resolution?
Keywords: Nagorno-Karabakh; Azerbaijan; Group of Minsk; OSCE; mediation; mediator’s impartiality; peaceful means of international disputes settlement